Nuclear waste : the 10,000-year challenge - Dolan, Edward F., 1924-; Scariano, Margaret (New York : Franklin Watts, 1990)
Examines the causes of nuclear waste, the threats it poses to human health and the environment, and efforts to regulate its disposal.
Includes bibliographical references (p. 145-156) and index.
Booklist.
Kirkus Review.
Wilson's Senior High School.
9-12.
Young Adult
Keywords: Radioactive pollution -- Environmental aspects -- Juvenile literature; Radioactive wastes -- Juvenile literature; Pollution; Radioactive pollution; Radioactive wastes; Hazardous wastes; Pollution; Radioactive pollution